2021
DOI: 10.24251/hicss.2021.544
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Operating in Many Realities on Memory: An Experiment on Memory Recognition in Extended Realities

Abstract: Extended reality (XR) such as VR and AR have been increasingly adopted across domains in cognitively challenging activities such as learning, shopping, and gaming among others. There are a few concerns about the inferior cognitive affordance of XRmediated functioning, e.g., with respect to memory retention. For better understanding how different XR technologies influence memory performance (e.g., recognition), we examine the effects of VR and ARmediation on the ability to remember (i.e., recognize afterward) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…where, who and when) AR can provide a superior or inferior shopping experience in terms of affective, cognitive, social, and behavioral outcomes. For example, the empirical evidence from Xi et al. (2021) revealed that a fully physical environment or the combination of AR and VR can provide better memory performance during shopping than using AR alone; AR might not be suitable for a certain group of shoppers given that it is associated with certain perceptual and cognitive skills (Peleg-Adler et al.…”
Section: Discussionmentioning
confidence: 99%
“…where, who and when) AR can provide a superior or inferior shopping experience in terms of affective, cognitive, social, and behavioral outcomes. For example, the empirical evidence from Xi et al. (2021) revealed that a fully physical environment or the combination of AR and VR can provide better memory performance during shopping than using AR alone; AR might not be suitable for a certain group of shoppers given that it is associated with certain perceptual and cognitive skills (Peleg-Adler et al.…”
Section: Discussionmentioning
confidence: 99%
“…Visual stimuli can trigger a previous experience by stimulating perceptual reenactment, enriched by other sensory stimuli (Zampini and Spence, 2004). XR can provide rich visual stimuli through an immersive environment and augment digital objects in the real world, making XR trigger tourists’ memories, both cognitively and affectively (Xi et al , 2021).…”
Section: Multisensory Extended Reality In Different Tourism Domains A...mentioning
confidence: 99%